Chiefs and government in post-colonial Zimbabwe: the case of Makoni District, 1980-2014 - Nkomo, Lotti (University of the Free State, 2015)
This study explores the relationship between chiefs and government in Zimbabwe during the period 1980-2014. It examines how the interactions between chiefs and government evolved over three and a half decades, with specific reference to the Makoni District of Manicaland Province. The abovementioned relationship was marked by three broad phases, namely 1980-1986, 1987-1999 and 2000-2014. The phases corresponded with variations in the political climate. These changes carry the central theme of the study, namely the way in which the relationship was informed by changing political imperatives. As the case of Makoni District reveals, chiefs were rejected by the independence government in 1980 for their perceived role as anti-nationalists; they were courted when political challenges began to appear in the late 1980s; and they were effectively co-opted when more powerful political threats emerged in 1999 with the rise of strong opposition politics. The defining features of the relationship evolved around the chiefs’ power over land and judicial affairs. At first, the chiefs were stripped of their judicial and land powers when their relationship with the government was characterised by hostility. These powers were restored when the government needed the chiefs’ political support. Using the case of Makoni chiefs, the aim of the study is to show how the ZANU PF government initially rejected and later co-opted chiefs in its administrative and political system for its hegemonic convenience.

Hierdie studie stel ondersoek in na die verhouding tussen hoofmanne en die regering in Zimbabwe gedurende die tydperk 1980-2014. Die soeklig val op hoe die interaksies tussen hoofmanne en die regering oor drie en ’n half dekades ontwikkel het, met spesifieke verwysing na die Makoni-distrik van die Manicaland-provinsie. Die bogenoemde verhouding het deur drie breë fases beweeg, naamlik 1980-1986, 1987-1999 en 2000-2014. Dié fases het ooreengestem met skommelinge in die politieke klimaat. Hierdie veranderings dra die sentrale tema van die studie, naamlik die wyse waarop die verhouding beïnvloed is deur veranderende politieke oorwegings. Soos die geval van Makoni-distrik aantoon, is die hoofmanne in 1980 deur die onafhanklikheidsregering verwerp as gevolg van hulle vermeende rol as anti-nasionaliste; in die laat 1980's het die regering toenadering gesoek toe politieke uitdagings op die horison verskyn het; en in 1999, toe ernstiger politieke bedreigings hul verskyning in die vorm van die opkoms van sterk opposisiepolitiek gemaak het, is hulle effektief gekoöpteer. Die bepalende kenmerke van die verhouding het om die hoofmanne se mag oor grond- en geregtelike sake gewentel. Aan die begin is die hoofmanne van hul geregtelike en grondverwante magte ontneem toe hulle verhouding met die regering deur vyandigheid gekenmerk is. Hierdie magte is herstel toe die regering die hoofmanne se politieke ondersteuning nodig gekry het. Met verwysing na die geval van die Makoni-hoofmanne is die mikpunt van die studie om aan te toon hoe die ZANU PF-regering hoofmanne aanvanklik verwerp en later in sy administratiewe en politieke stelsel gekoöpteer het in die najaag van sy hegemoniese aspirasies.
Dissertation (M.A. (Centre for Africa Studies))--University of the Free State, 2015
Keywords: ZANU PF; Makoni District; Chiefs; Government; Post-colonial